1996
DOI: 10.1046/j.1365-2141.1996.424984.x
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic marrow transplantation for aplastic anaemia associated with dyskeratosis congenita

Abstract: Eight patients with aplastic anaemia associated with dyskeratosis congenita received allogeneic marrow grafts from either HLA-identical siblings (six patients) or HLA-matched unrelated donors (two patients). Patients who received marrow from HLA-identical siblings were conditioned with cyclophosphamide (140-200 mg/kg), with or without antithymocyte globulin. Patients who received unrelated donor marrow were conditioned with cyclophosphamide (120 mg/kg) and total body irradiation (1200 cGy). The six patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 32 publications
0
56
0
2
Order By: Relevance
“…Various regimens have been examined, but there is not yet a commonly accepted standard. 9,12,14,[18][19][20][21][22][23][24][25][26][27][28][29][30] Table 3 summarizes the reported experience of HCT for patients with DC using reducedintensity conditioning, including specifics of donors, regimens and outcomes. Kaplan-Meier analysis revealed that overall cumulative survival was 65%, with related donor recipients having better survival compared with unrelated donor transplants (91 vs 30%, respectively, P ¼ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Various regimens have been examined, but there is not yet a commonly accepted standard. 9,12,14,[18][19][20][21][22][23][24][25][26][27][28][29][30] Table 3 summarizes the reported experience of HCT for patients with DC using reducedintensity conditioning, including specifics of donors, regimens and outcomes. Kaplan-Meier analysis revealed that overall cumulative survival was 65%, with related donor recipients having better survival compared with unrelated donor transplants (91 vs 30%, respectively, P ¼ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports (Table 3) have described progression of the clinical signs of DKC after transplantation, which was indistinguishable from the natural course of disease. [8][9][10][11][20][21][22][23] In our series, all patients except one received low intensity conditioning regimens. The conditioning protocol was different across different centers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the tolerability of the conditioning regimen is always limited by the increased risk of developing significant tissue injury as a result of irradiation and chemotherapy due to inherited defects in genome maintenance. [18][19][20][21][22][23] This hypersensitivity to irradiation and chemotherapy translated into poor survival of patients after SCT, using conventional myeloabaltive conditioning. 20,21 Short-term transplant-related complications are not uncommonly observed in patients with DKC in the setting of allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of allogeneic bone marrow transplantation in these patients have been relatively poor due to early and late complications. [6][7][8][9][10] We describe the effect of bone marrow transplantation for aplastic anemia in two siblings with dyskeratosis congenita from a single donor. The other brother of these two siblings had died due to bone marrow failure and dyskeratosis congenita previously.…”
mentioning
confidence: 99%